A Reflection on Habitual Belief and Habitual Doubt - Irene Papoulis (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
Some people are habitual "believers" while others are habitual "doubters." I' m a believer, but doubting others helps me believe myself I explore the idea that examining our individual habitual relationships with believing and doubting helps us think better and relate better to others and to ourselves.